Decomposing decomposition: isolating direct effects of temperature from other drivers of detrital processing. Issue 10 (8th August 2021) - Wilmot, Oliver J.; Hood, James M.; Huryn, Alexander D.; Benstead, Jonathan P.
Abstract: Understanding the observed temperature dependence of decomposition (i.e., its "apparent" activation energy) requires separation of direct effects of temperature on consumer metabolism (i.e., the "inherent" activation energy) from those driven by indirect seasonal patterns in phenology and biomass, and by longer‐term, climate‐driven shifts in acclimation, adaptation, and community assembly. Such parsing is important because studies that relate temperature to decomposition usually involve multi‐season data and/or spatial proxies for long‐term shifts, and so incorporate these indirect factors. The various effects of such factors can obscure the inherent temperature dependence of detrital processing. Separating the inherent temperature dependence of decomposition from other drivers is important for accurate prediction of the contribution of detritus‐sourced greenhouse gases to climate warming and requires novel approaches to data collection and analysis. Here, we present breakdown rates of red maple litter incubated in coarse‐ and fine‐mesh litterbags (the latter excluding macroinvertebrates) for serial approximately one‐month increments over one year in nine streams along a natural temperature gradient (mean annual: 12.8°–16.4°C) from north Georgia to central Alabama, USA. We analyzed these data using distance‐based redundancy analysis and generalized additive mixed models to parse the dependence of decomposition rates on temperature, seasonality, and shredding macroinvertebrate biomass. Microbial decomposition in fine‐mesh bags was significantly influenced by both temperature and seasonality. Accounting for seasonality corrected the temperature dependence of decomposition rate from 0.25 to 0.08 eV. Shredder assemblage structure in coarse‐mesh bags was related to temperature across both sites and seasons, shifting from "cold" stonefly‐dominated communities to "warm" communities dominated by snails or crayfish. Shredder biomass was not a significant predictor of either coarse‐mesh or macroinvertebrate‐mediated (i.e., coarse‐ minus fine‐mesh) breakdown rates, which were also jointly influenced by temperature and seasonality. Unlike fine‐mesh bags, however, temperature dependence of litter breakdown did not differ between models with and without seasonality for either coarse‐mesh (0.36 eV) or macroinvertebrate‐mediated (0.13 eV) rates. We conclude that indirect (non‐thermal) seasonal and site‐level effects play a variable and potentially strong role in shaping the apparent temperature dependence of detrital breakdown. Such effects should be incorporated into studies designed to estimate inherent temperature dependence of slow ecological processes.